Integrating a novel irrigation approximation method with a process-based remote sensing model to estimate multi-years' winter wheat yield over the North China Plain - Sha ZHANG; Shan-shan YANG; Jing-wen WANG; Xi-fang WU; Malak HENCHIRI; Tehseen JAVED; Jia-hua ZHANG; Yun BAI (Journal of Integrative Agriculture, 2023)
Accurate estimation of regional winter wheat yields is essential for understanding the food production status and ensuring national food security. However, using the existing remote sensing-based crop yield models to accurately reproduce the inter-annual and spatial variations in winter wheat yields remains challenging due to the limited ability to acquire irrigation information in water-limited regions. Thus, we proposed a new approach to approximating irrigations of winter wheat over the North China Plain (NCP), where irrigation occurs extensively during the winter wheat growing season. This approach used irrigation pattern parameters (IPPs) to define the irrigation frequency and timing. Then, they were incorporated into a newly-developed process-based and remote sensing-driven crop yield model for winter wheat (PRYM–Wheat), to improve the regional estimates of winter wheat over the NCP. The IPPs were determined using statistical yield data of reference years (2010–2015) over the NCP. Our findings showed that PRYM–Wheat with the optimal IPPs could improve the regional estimate of winter wheat yield, with an increase and decrease in the correlation coefficient (R) and root mean square error (RMSE) of 0.15 (about 37%) and 0.90 t ha–1 (about 41%), respectively. The data in validation years (2001–2009 and 2016–2019) were used to validate PRYM–Wheat. In addition, our findings also showed R (RMSE) of 0.80 (0.62 t ha–1) on a site level, 0.61 (0.91 t ha–1) for Hebei Province on a county level, 0.73 (0.97 t ha–1) for Henan Province on a county level, and 0.55 (0.75 t ha–1) for Shandong Province on a city level. Overall, PRYM–Wheat can offer a stable and robust approach to estimating regional winter wheat yield across multiple years, providing a scientific basis for ensuring regional food security.